APLIKASI VOTING PEMILIHAN KETUA ORGANISASI SISWA INTRA SEKOLAH (OSIS) PADA MA NURUL IHSAN NW TILAWAH BERBASIS WEB - Mohammad Taufan Asri Zaen; Ryadi Putra (Jurnal Manajemen Informatika dan Sistem Informasi, 2018)
In the world of education, technology plays very important role to support the teaching and learning process and activities in the school, but not all of the process activities accommodated by the development of technology. The process of election of OSIS MA Nurul Ihsan NW Tilawah, a system that everything is done still conventional, all the process is done manually and it is less effective and efficient. Voting (E-Voting) applications are considered to be more effective and more efficient because all of the process is computerized, making it easier for users to choose candidates, simplify the vote counting process and the results of the election can be known quickly and accurately.The manufacture and application design of voting election of the OSIS on MA Nurul Ihsan NW Tilawah based website was built using development methods system development life cycle (SDLC), programming languages PHP and using MySQL database. The data that will be managed in the system are committee data, voter or student data, candidate data or candidate OSIS with the registration process and selection process. The output of this application design is the voter data report, the candidate data report and the voting voice data report.This voting application at MA Nurul Ihsan NW Tilawah is expected to facilitate the process of electing the student council president, and giving voting results that are accurate, fast and reliable and can reduce the number of students who do not vote and will not interfere with the teaching and learning process